THE ANALYSIS OF GRAMMATICAL PROBLEMS AND GENERIC STRUCTURE OF NARRATIVE TEXT WRITTEN BY THE ELEVENTH GRADUATE STUDENTS OF LANGUAGE PROGRAM AT SMAK ST.KLAUS WERANG-WEST FLORES - Yosefina Elsiana Suhartini (Unika Santu Paulus Ruteng, 2019)
The study was intended to analyze grammatical problem and generic structures of narrative text written by the eleventh grade students of Language program at SMAK St. Klaus–West Flores in the academic year 2016/2017. The data were mainly collected through assigment on narrative written text and itervies and were analyzed descriptively using Dulay’lingistics taxonomy (1982) and Fink’ category (2005). The result of data analysis revealed that the students committed errors in their narrrative writing, namely article, possessive case, omission of – ed, regularization by adding –ed, simple present tense used in place of simple past tense, omission of –be, pluralization, pronoun, preposition, omission of main verb, subject verb agreement, word order, diction, spelling, passive form, adverb, conjunction, double marking, and modals. The cause of error was interference, lack of vocabularies, and motivation, and teacher’ ability/qualification.